Malaysia : from crisis to recovery - Meesook, Kanitta...[et al.] (IMF WashingtonUS, 2001)
Reviews policy issues and aspects of economic management that have been associated with Malaysia's progress from a major crisis to a strong recovery, and their implications for the future.